2013
DOI: 10.3758/s13428-013-0414-2
|View full text |Cite
|
Sign up to set email alerts
|

The scene and the unseen: Manipulating photographs for experiments on change blindness and scene memory

Abstract: The change blindness paradigm, in which participants often fail to notice substantial changes in a scene, is a popular tool for studying scene perception, visual memory, and the link between awareness and attention. Some of the most striking and popular examples of change blindness have been demonstrated with digital photographs of natural scenes; in most studies, however, much simpler displays, such as abstract stimuli or "free-floating" objects, are typically used. Although simple displays have undeniable ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…traffic, when suprathreshold stimuli can be easily missed (as shown by e.g. change blindness experiments 3 5 ). To summarize, while physical effectiveness can determine MSF in simple paradigms, internal and physical effectiveness might determine MSF in more complex paradigms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…traffic, when suprathreshold stimuli can be easily missed (as shown by e.g. change blindness experiments 3 5 ). To summarize, while physical effectiveness can determine MSF in simple paradigms, internal and physical effectiveness might determine MSF in more complex paradigms.…”
Section: Discussionmentioning
confidence: 99%
“…To test which factors optimally predict the label of MSF for each participant (hypotheses 4–5), we conducted a modelling analysis. To this end, we modelled our data on the basis of a generalized linear regression using the glmfit function in Matlab 3 . Analyses were run separately for dʹ and RT scores.…”
Section: Methodsmentioning
confidence: 99%
“…However, effects of such image features on visual perception and stimulus-evoked neuronal responses are well known. Consequently, it is recommended to carefully control the physical properties of visual stimulus material (Knebel et al, 2008; Willenbockel et al, 2010; Kovalenko et al, 2012; Ball et al, 2013). For example, the role of image complexity and spatial frequencies for neural responses are heavily debated in the field of face processing (Vuilleumier et al, 2003; Thierry et al, 2007; Rossion and Jacques, 2008) and are increasingly considered during affective picture viewing (Bradley et al, 2007; Delplanque et al, 2007; Wiens et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, this intuition has been challenged by results obtained with the "change blindness" paradigm (see Rensink, 2002;Simons & Rensink, 2005, for reviews). This line of research has demonstrated that observers are surprisingly poor at detecting substantial changes in a scene if the change occurs simultaneously with a brief visual disruption, be it a saccade (McConkie & Currie, 1996;Hayhoe et al, 1998), an eye blink (O'Regan et al, 2000), a flicker (Ball et al, 2013;Rensink et al, 1997), or a distracting stimulus (O'Regan et al, 1999). Under these conditions, change detection cannot be based on detecting a motion or contrast transient, but depends on encoding, preserving, and comparing object representations of pre-change and post-change objects.…”
Section: Introductionmentioning
confidence: 99%